Mysmenidae (Arachnida, Araneae), a spider family newly recorded from Vietnam - Lin, Yucheng; Li, Shuqiang (Zootaxa, 2014)
The spider family Mysmenidae is reported from Vietnam for the first time. Both sexes of three new species are described: Calodipoena tamdaoensis n. sp. from Tam Dao National Park, Gaoligonga taeniata n. sp. and Mysmena maculosa n. sp. from Cuc Phuong National Park. Morphological descriptions, diagnoses and comparative illustrations are provided.